2016
DOI: 10.1021/acs.jpca.6b02699
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanism of Oxidation of Methimazole by Chlorite in Slightly Acidic Media

Abstract: The kinetics and mechanism of the oxidation of methimazole (1-methyl-3H-imidazole), MMI, by chlorite in mildly acidic environments were studied. It is a complex reaction that gives oligo-oscillations in chlorine dioxide concentrations in excess chlorite conditions. The stoichiometry is strictly 2:1, with the sulfur center being oxidized to sulfate and the organic moiety being hydrolyzed to several indeterminate species. In excess MMI conditions over chlorite, the sulfinic acid and sulfonic acid were observed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…system, therefore the absence of this group will retard the reaction pathway. So, it can be concluded that this method can be considered as a stability-indicating method for methimazole determination (7).…”
Section: Kinetics Of the Reactionsmentioning
confidence: 88%
See 2 more Smart Citations
“…system, therefore the absence of this group will retard the reaction pathway. So, it can be concluded that this method can be considered as a stability-indicating method for methimazole determination (7).…”
Section: Kinetics Of the Reactionsmentioning
confidence: 88%
“…It was found that the ratio was 1.439:1.13 pointing out to a ratio of 1:1 (KMnO4 to Methimazole). Accordingly, the reaction pathway is suggested to proceed as [7]: According to the suggested mechanism of oxidation, the method is based on the presence of the thiol group which is oxidized by the MnO4 -/OH -…”
Section: Methods Amentioning
confidence: 99%
See 1 more Smart Citation
“…We tested the silyl enol ether trap’s ability to distinguish between tautomers generated in the aqueous peroxidation of methimazole, 9 , Scheme . A recent report suggested sulfenyl 10 and S-oxide 11 tautomers, but not the sulfinyl 12 . In the absence of a trap, the nominal sulfenic acid mass is seen, attributable to any tautomer.…”
mentioning
confidence: 89%
“…A recent report suggested sulfenyl 10 and S-oxide 11 tautomers, but not the sulfinyl 12. 26 In the absence of a trap, the nominal sulfenic acid mass is seen, attributable to any tautomer. However, in the presence of the 1- trimethylsiloxycyclohexene, adducts attributable to all three tautomers are observed as shown in Figure 3; quantification of the SIC areas assigned to tautomers 10, 11, and 12 gives a relative abundance as 100:54:1, respectively.…”
mentioning
confidence: 99%